Letter from the Editor: Reviewers Needed - Jeri W Dunkin (Rural Nurse Organization; Binghamton University, 2006)
The Online Journal of Rural Nursing and Health Care is the official Journal of the Rural Nurse Organization. It is an electronic journal and can be accessed at http://www.rno.org/journal/index.htm. It is a refereed journal and is indexed in CINAHL and has an international readership. To complete the review processes necessary for a refereed journal there must be a volunteer panel of reviewers to judge the quality and appropriateness of submissions for publication. The review panel has international members and the published articles are from around the world. However, as peoples' lives change their ability to provide this valuable service to the Online Journal of Rural Nursing and Health Care changes. That leaves the editorial in constant need of committed reviewers. If you would be interested in serving on the review panel of the Online Journal of Rural Nursing and Health Care please email a note of interest and your resume to the Editor, Dr. Jeri Dunkin, at jdunkin@bama.ua.edu.